Le prime opere narrative di Don DeLillo Rappresentazione del tempo e poetica beckettiana dell'istante - Barbuscia, Davide (Premio Ricerca «Città di Firenze», 2013)
This study deals with the first works by Don DeLillo, from Americana (1971) to Running Dog (1978), but it also extends its investigation horizon to his following works. The work deals specifically with the conception of time, and the way it is represented in the texts of the American author. By integrating the philosophy of time with narratology, the volume offers critical reflections aimed at identifying the type of poetics through which DeLillo articulates time in his work. In particular, the centrality of the perception of time in his novels and, more specifically, the concentration of the plots in certain moments, the oblique presence of the influence of Samuel Beckett's work in the representation of duration and the attention of the author to the double temporality of the cinematographic image and its hidden aesthetic potential are highlighted. Therefore, time becomes the conceptual context in which the textures of these texts, and the themes characterising them, find a resolution. In the representation of time, in the microscopic analysis and in the slow motion of some specific time segments, DeLillo's narrative traces the possibilities of an indefinable and mysterious perception of reality and history.